The roared-at boys? Repertory casting and gender politics in the RSC's 2014 Swan season - Kirwan, Peter (Taylor and Francis, 2015)
This essay interrogates the loading of the “Roaring Girls” season by asking what it means to “roar” in both the early modern period and twenty-first century, unpacking the terms on which the women of these productions are empowered or undermined through their treatment by their male counterparts. Performed alongside the 2014 “Midsummer Mischief” new writing season, the plays reposition “roaring” as challenging male-centred modes of representation. Drawing on Marvin Carlson's influential work on “ghosting”, this essay addresses these questions through investigation of the practices and implications of ensemble casting. With Arden of Faversham, The Roaring Girl and The White Devil sharing a single ensemble, the iterated roles of actors across the ensemble become key to understanding the season's overall strategies for presenting and interrogating misogyny. The recycling of actors’ bodies throws into relief the individual roles of the main “roaring girls”, framing and articulating the role of mischievous disruption within the company's work.